Physical activity among adults with type 2 diabetes mellitus in Jordan: a qualitative study - Aaliyah Momani; Zalikha Al-Marzouqi; Amani Abu-Shhadeh; Kamel Ajlouni; Mohammed ALBashtawy; Maysa H. Almomani; Samiha Jarrah; Shaikha Ali AlQahtani; Anas Ababneh (Therapeutic Advances in Endocrinology and Metabolism)
Background: Type 2 diabetes mellitus is a growing epidemic condition that is expected to reach pandemic levels in the upcoming decades. Physical activity among individuals with type 2 diabetes is beneficial. A deeper understanding of physical activity among adults with type 2 diabetes in Jordan using a qualitative approach is needed. Aim: This study aimed at exploring physical activity among adults with type 2 diabetes in Jordan. Design: A constructivist grounded theory methodology guided this study. Methods: Data were collected using semi-structured and audio-recorded interviews and then analysed simultaneously using coding, constant comparative analysis and writing reflexive memos. Findings: Two themes emerged including ‘The Perception about Physical Activity’ and ‘Factors Influencing Adherence to Physical Activity’. The first theme included four sub-themes: physical activity definition; importance; duration and types. The second theme included five sub-themes: the belief that diet is superior to physical activity; ageing and presence of diabetes or comorbidities; job and family obligations; social support and weather. Conclusion: This study provided insights into patients’ perceptions and adherence to physical activity including facilitators and barriers. Clinicians and policymakers may consider the findings of this study to develop health promotion programmes and to suggest a suitable environment for individuals with type 2 diabetes to enhance their physical activity.